Inovasi Stik Bawang dengan Penambahan Daun Kelor (Morina oleifera L.) - Maulid Nabila; Ita Fatkhur Romadhoni; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Onion sticks are a snack that is flat, long and resembles a stick and has a distinctive savory taste and crispy texture which is finally processed through frying. Moringa leaves are a plant with a multitude of benefits, including lowering blood sugar levels, controlling inflammation, controlling blood pressure, maintaining healthy growth and brain cells, inhibiting cancer, and increasing body resistance. The research objectives were to determine: 1) The results of the sensory quality of onion sticks with the addition of Moringa leaves, including color, taste, aroma, texture and level of preference; 2) Value of the vitamin C content of Moringa leaf sticks based on the best sensory results; 3) Selling price of Moringa leaf sticks in packages weighing 250 grams/package. This research is an experiment in making onion sticks with the addition of Moringa leaves. Using the observation method through sensory quality testing with 30 panelists. The resulting data was processed using the Anova test followed by the Duncan test. To determine the nutritional content of vitamin C, laboratory tests are carried out. The results of the research showed: 1) The best formulation of onion sticks with the addition of Moringa leaves from the sensory test was obtained from the addition of 20 grams of Moringa leaves. 2) The nutritional content of vitamin C in the product is 102.60 mg/100 gr. 3) The selling price of Moringa leaf sticks is known to be IDR 27.650 per-package weighing 250 grams.